Mechanical Properties of Recycle Polymers Reinforcement with Glass Fiber Composite Material - Md Fadil, Muhammad Fareed Hafizuddin; Hashim, Mohd Yusni (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Glass fiber are commonly use in this industry application for some manufacturing product. As we know waste polymer is a big issue for our country. Recycled polymer will affect our environmental problem. In this review paper, research about the recycled polymer is mixing with glass fiber to form a new specimen with higher strength than before. Method that had been used to mix this product is Brabender Plastograph and the polymer will be inject by injection molding to for a new specimen followed the standard. As the review that have been research the polymer for (PET Polyethylene Terephthalate) and PP (Polypropylene) this product is analyze their characteristic to perform a new material. Next, several types of fiber are research to know their specific characteristic that suitable for mixing the polymer. The main objective for this review is to review the mechanical strength of reinforce carbon polymer by using tensile, impact & flexural test and to study the suitable percentage ratio of reinforcement between glass fiber and polymer. The percentage of fiber and polymer had been research very specifically to form a new specimen. The method of mixing is using the Brabender Plastograph for mixing with using percentage of weight. After mixing injection molding is used to form a specimen to follow standard material and tested by using flexural and tensile test to find out their strength. The percentage below 10% is most suitable and the value for glass fiber compared to polymer.  The result for tensile test is had increase their strength around 43% and flexural increase around 47% when mixing with glass fiber which is better than before. Therefore, the waste polymer will be recycled to form a new specimen with higher strength and useful for future.